The Sociolinguistic Landscape of Language Representation in Pakistani Television Dramas: A Critical Discourse Analysis - Nawaz, Muhammad Haseeb; Yali, Zhu; Ikhlaq, Muhammad (Pakistan Languages and Humanities Review, 2023)
Pakistani society is a patriarchal society in which culture, norms, traditions, and social sectors are powerfully and intensely entrenched in the society. Pakistani Television Dramas talk about sensitive social wrongs of the society. This study takes a critical discourse analysis approach aimed to find the sociolinguistic landscape in selected Pakistani drama ‘Baghi’ and the dominant influence with the use of language. The purpose of this study was to critically analyze the use of language and the representation of ideologies. A laborious methodological method has been opted to carry out critical discourse analysis of the drama for the research. The researcher has used qualitative method, because its purpose is to do a detailed and rich textual analysis of Pakistani TV drama based on reality. The data was collected based on the utterances taken from the episodes of drama which specifically signify skillful use of language. The analysis was based on the Fairclough’s three-dimensional model (1992) and linguistic modalities (Fairclough, 2003). The study and the findings of the research showed that how language is used by the social actors of the drama to address different dimensions. The study revealed that representation of honor, shame and patriarchy is a dominant and prevailing aspect of Pakistani culture and norms. Justification of human rights in general and particularly of women is neglected in a typical Pakistani stereotypical society as; powerful people know how to use power with the use of language. It has also concluded t at the drama Baghi throws the light on the power relations which exists between man and h woman. In the drama, man has been portrayed as a symbol of power and authority.